The funerary monuments of the Silla del Papa (Tarifa, Cadiz), 2nd-1st century BC: architectural, archaeological and historical study - (:unkn) unknown (My University, 2021)
The Strait of Gibraltar is a strategic area located at the crossroads between Africa, Europe, the Mediterranean Sea and the Atlantic. In the 2nd - 1st century BC, it experienced a period of turmoil due to the second Punic War and the civil wars of the Roman Republic. However, this period remains poorly documented by archaeology. Recent excavations at the oppidum of La Silla del Papa (Tarifa, Cadiz) have revealed two cemeteries containing lapidary remains of a funerary architecture that can fill in part of this gap. This new corpus includes more than three hundred architectural blocks (erratic or reused in later constructions), as well as several dozen structures in place. In the first part of this thesis, the analysis of the architectural data leads to the identification of several types of monuments and decorations. This first step allows, in a second phase, to compare the funerary architecture of the Silla del Papa with contemporary monuments in the Mediterranean context. This comparative analysis is essential to understand the interrelations that took place in the area of the Strait of Gibraltar and to propose reconstructions of the monuments. Finally, the results obtained are placed in their historical context, highlighting the moments of rupture constituted by the Second Punic War and the Sertorian conflict, the North African influences, and the complexity of the Romanisation process.
Keywords: African Research